Fatal leptospirosis in southern sea otters from Central California: pathologic findings and detection of Leptospira interrogans - Margaret E. Martinez; Pádraig J. Duignan; Katherine C. Prager; Cara L. Field; Mary E. Gomes; Rinosh Mani; Lilian Carswell; Tim Tinker; Joseph Tomoleoni; Michael Murray; Ri K. Chang; James O. Lloyd-Smith; et al. (Frontiers in Marine Science, 2026)
Leptospira interrogans serovar Pomona infections cause periodic outbreaks in California sea lions (CSLs; Zalophus californianus ) and sporadic deaths in phocids. However, the frequency of infection and associated health impacts remain uncharacterized in sympatric threatened southern sea otters (SSOs; Enhydra lutris nereis ), which serve as important sentinels of coastal health. Given the broad impacts of L. interrogans on other marine mammals, our objective was to screen selected SSOs for infection, determine whether leptospirosis contributes to SSO mortality, and describe leptospiral-associated lesions. A retrospective review (2005–2025) identified 19 candidate cases that underwent detailed review, including Leptospira immunohistochemistry (IHC), serology, and polymerase chain reaction (PCR), with a special focus on renal and hepatic lesions. Kidney samples were PCR-positive for 74% (14/19) of suspected cases. For eight of these, DNA sequence-based serogroup typing detected L. interrogans serogroup Pomona. Seven of the 14 PCR-positive leptospirosis cases were classified as fatal based on positive renal IHC and moderate to severe tubulointerstitial nephritis. All fatal cases had anti- L. interrogans serovar Pomona antibody titers ≥1:25,600. The remaining seven PCR-positive cases were considered nonfatal leptospirosis due to minimal and/or unrelated renal lesions and negative IHC. Nonfatal Leptospira -infected cases ranged from seronegative to low positive (1:400) for serovar Pomona. Antibody titers for Leptospira PCR-negative cases were negative. In fatal cases, gross renal changes were often inapparent or characterized by miliary white cortical foci. Renal histologic lesions included tubulointerstitial nephritis, acute tubular necrosis, and suppurative tubulitis with intratubular bacteria, along with positive IHC staining for leptospiral antigen in the lesions. Gross hepatic changes were also inapparent in fatal cases, and histologic lesions were rare, characterized in one animal by hepatocellular dissociation and in two sea otters by limited leptospiral antigen detection by IHC. Most Leptospira -infected sea otters (71%, 10/14) stranded during higher rainfall months in California, suggesting possible land-to-sea transmission from terrestrial hosts. Given these findings, and because L. interrogans serovar Pomona infections have been confirmed in sympatric CSLs and terrestrial mammals from adjacent watersheds, a focused investigation of potential marine and terrestrial disease transmission dynamics could provide new information to reduce SSO mortalities.

Spatiotemporal changes of atmospheric depositions over 43 years in south-central Ontario - Huaxia Yao; Joelle Young; April James; David Lembcke; Christopher McConnell; Tim Field; Lance Aspden; Sara Rawski; Chris Jones; Michelle Palmer; Claire Holeton; James A. Rusak; et al. (Atmospheric Environment, 2025)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Multifarious anchovy and sardine regimes in the Humboldt Current System during the last 150 years - Renato Salvatteci; David Field; Dimitri Gutiérrez; Tim Baumgartner; Vicente Ferreira; Luc Ortlieb; Abdel Sifeddine; Daniel Grados; Arnaud Bertrand (Global Change Biology, 2018)
The Humboldt Current System ( HCS ) has the highest production of forage fish in the world, although it is highly variable and the future of the primary component, anchovy, is uncertain in the context of global warming. Paradigms based on late 20th century observations suggest that large‐scale forcing controls decadal‐scale fluctuations of anchovy and sardine across different boundary currents of the Pacific. We develop records of anchovy and sardine fluctuations since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine phases with a timescale that is not consistent with previously proposed periodicities. Rather, the regime shifts in the HCS are related to 3D habitat changes driven by changes in upwelling intensity from both regional and large‐scale forcing. Moreover, we show that a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity in the HCS .

The seasonal structure of microbial communities in the Western English Channel - Jack A. Gilbert; Dawn Field; Paul Swift; Lindsay Newbold; Anna Oliver; Tim Smyth; Paul J. Somerfield; Sue Huse; Ian Joint (Environmental Microbiology, 2009)
Summary Very few marine microbial communities are well characterized even with the weight of research effort presently devoted to it. Only a small proportion of this effort has been aimed at investigating temporal community structure. Here we present the first report of the application of high‐throughput pyrosequencing to investigate intra‐annual bacterial community structure. Microbial diversity was determined for 12 time points at the surface of the L4 sampling site in the Western English Channel. This was performed over 11 months during 2007. A total of 182 560 sequences from the V6 hyper‐variable region of the small‐subunit ribosomal RNA gene (16S rRNA) were obtained; there were between 11 327 and 17 339 reads per sample. Approximately 7000 genera were identified, with one in every 25 reads being attributed to a new genus; yet this level of sampling far from exhausted the total diversity present at any one time point. The total data set contained 17 673 unique sequences. Only 93 (0.5%) were found at all time points, yet these few lineages comprised 50% of the total reads sequenced. The most abundant phylum was Proteobacteria ( 50% of all sequenced reads), while the SAR11 clade comprised 21% of the ubiquitous reads and ∼12% of the total sequenced reads. In contrast, 78% of all operational taxonomic units were only found at one time point and 67% were only found once, evidence of a large and transient rare assemblage. This time series shows evidence of seasonally structured community diversity. There is also evidence for seasonal succession, primarily reflecting changes among dominant taxa. These changes in structure were significantly correlated to a combination of temperature, phosphate and silicate concentrations.

Geostatistical analysis of biomarkers of genotoxicity in cattle, Bos taurus and Bos taurus × Bos indicus, sentinels near industrial facilities - Wesley Bissett; Roger Smith; L. Garry Adams; Robert Field; William Moyer; Tim Phillips; H. Morgan Scott; James A. Thompson (Ecotoxicology, 2009)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Effects of a low dose of alcohol on cognitive biases and craving in heavy drinkers - Tim Schoenmakers; Reinout W. Wiers; Matt Field (Psychopharmacology, 2008)